Micropulse transcleral laser cycloplasty (mTLC) should replace the term “micropulse cyclophotocoagulation (mCPC)” - I. E. Ioshin (Российский офтальмологический журнал, 2024)
Purpose: the article presents arguments for changing the traditional operation name “micropulse cyclophotocoagulation”. In accordance with the potential mechanisms involved, a new name is proposed — “micropulse transscleral laser cycloplasty”.